ANALISIS POLA TABUHAN MUSIK IRINGAN TARI SIGAL DALAM PERAYAAN GAWAI DAYAK BIDAYUH KABUPATEN BENGKAYANG - Firdaus, Firdaus; Fretisari, Imma; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research based to knowPunch Pettern in Sigal Dance Accompaniment Music on Gawai DayakBidayuh Celebration at Bengkayang.This research used descriptive analysis method, qualitative research and etnomusicology approach. Sources of data in this study the from of interviews with relevant sources. Data collection techniques such as observation, interviews, study literature and documentation. Technique validity of data used was source triangulation, triangulation technique and lengthen observation. Data analysis techniques in this study, that was transcribe Punch Pettern in Sigal Danceinto music notation.Based on data analysis wasSigal dance accompaniment it?s music punch structure in the accompaniment of dancebased on punch pettern.It was instrumentOguang, Sanang, Klutang, Kitaak dan Pidabat which is played out used a wooden stick but especially for Pidabat instrument used palms and wooden sticks. Sigal  start fromKlutang instrument proceed with Sanang instrument followed next Oguang and Kitaak instrument then the last Pidabat instrument. The Sigal dance accompaniment music comes from Jagoi Babang. Punch pettern the Sigal dance accompaniment music have the quality Ostinanto from beginning punch unchanged to the end. The result expected to be implented in the learning design of eighth grade first semester about Punch Pettern in Sigal Dance.Key Words: Pidabat, Punch Pattern, Sigal Dance Accompaniment